2020
DOI: 10.1002/brb3.1628
|View full text |Cite
|
Sign up to set email alerts
|

Gene–disease association study of tumor necrosis factor‐α G‐308A gene polymorphism with risk of major depressive disorder: A systematic review and meta‐analysis

Abstract: MDD is a common and debilitating mood disease in the world characterized by pervasive and persistent low mood. It is accompanied by psychological and physiological symptoms, such as lack of motivation, changes in appetite, inability to feel pleasure, cognitive difficulties, and retraction from social interaction (Chan, Cathomas, & Russo, 2019). The proportion of the global population living with MDD is estimated to be 4.4%, representing the primary cause of disability worldwide (Zhao, Li, Tian, Zhu, & Zhao, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A number of genetic-related factors, genomic regions, polymorphisms, and other related aspects have been examined with respect to depression [ 61 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ,...…”
Section: Resultsmentioning
confidence: 99%
“…A number of genetic-related factors, genomic regions, polymorphisms, and other related aspects have been examined with respect to depression [ 61 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ,...…”
Section: Resultsmentioning
confidence: 99%
“…MDD affects more than 300 million people worldwide and causes severe social and economic burden ( 2 ). Genetic factors confer some heritable risk of MDD, while structural and neurochemical deficits in brain regions and exposure to traumatic or repeated psychosocial and environmental stressors can increase vulnerability to MDD or induce depressive symptoms ( 3 , 4 ). Depression is a multifactorial and heterogeneous disease with overlapping causal pathways, its pathogenesis has not been completely elucidated so far.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Nonetheless, a recent systematic review and meta-analysis revealed that neither the genotypes of the TNF-α G308A gene nor allele frequencies might represent an independent risk factor of depression. 41 TNF-α contributes to brain development, particularly by modulating hippocampal growth and function. 42,43 However, in several disorders, increased levels of this cytokine activate microglia, which then leads to demyelination and/or neuronal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 40 Nonetheless, a recent systematic review and meta‐analysis revealed that neither the genotypes of the TNF‐α G308A gene nor allele frequencies might represent an independent risk factor of depression. 41 …”
Section: Discussionmentioning
confidence: 99%